Bistatic systems - Elminowicz, Andrzej; Zajączkowski, L. (Archives of Acoustics, 2006)
This paper describes key features of a bistatic operation in the hydroacoustic systems, hisperformance model and constraints imposed by environment and propagation conditions inshallow water. The architecture and construction of bistatic systems, their features and requirementshas been presented. The application of bistatic systems, especially in protectionsystems, has been presented as barriers protecting anchorage or harbour, barriers protectingstraits or entries to the harbour. Attention was paid on possibility of cooperation among existing,commonly available sonars and bistatic acoustics devices.